The Spatial Thinking Workbook: A Research-Validated Spatial Skills Curriculum for Geology Majors. Issue 4 (1st November 2017) - Ormand, Carol J.; Shipley, Thomas F.; Tikoff, Basil; Dutrow, Barbara; Goodwin, Laurel B.; Hickson, Thomas; Atit, Kinnari; Gagnier, Kristin; Resnick, Ilyse
ABSTRACT: Spatial visualization is an essential prerequisite for understanding geological features at all scales, such as the atomic structures of minerals, the geometry of a complex fault system, or the architecture of sedimentary deposits. Undergraduate geoscience majors bring a range of spatial skill levels to upper-level courses. Fortunately, spatial thinking improves with practice, and students benefit from intentional training. Several promising teaching strategies have emerged from recent cognitive science research into spatial thinking: gesturing, predictive sketching, and comparison, including analogy and alignment. Geoscience educators have traditionally incorporated many of these tools in their teaching, though not always consciously, intentionally, and in the most effective ways. Our research team, composed of geoscientists and cognitive psychologists, has collaborated to develop curricular materials for mineralogy, structural geology, and sedimentology and stratigraphy courses that incorporate these strategies intentionally and purposefully, supporting student understanding of the spatially challenging concepts and skills in these courses. Collectively, these two dozen learning activities comprise the Spatial Thinking Workbook (http://serc.carleton.edu/spatialworkbook/index.html ). Pre- to posttest gains on a suite of assessment instruments, as well as embedded assessments, show that these curricular materials boost students' spatial thinking skills and strengthen their ability to solve geological problems with a spatial component.